From the historical-conceptual limitations of the presentation of the entropy in the books of physics of higher education to a proposal of education grounded in historical facts - Ribeiro da Cunha, Jefferson Adriany; Roversi Genovese, Luiz Gonzaga [UNESP]; de Queiros, Wellington Pereira [UNESP] (My University, 2018)
Through the Content Analysis we carried out an investigation of the didactic proposal existing in several texts of Higher Education Physics on the introduction of the Entropy concept. In this analysis and cataloging of the texts we highlight two dimensions of didactic and methodological approach, used by the texts for the presentation of entropy, which are: Strategy of definitions and Strategy of contextualization. Through several theoretical references in the area of History and Philosophy of Science we verified that the physical concepts can also be worked through a didactic strategy that takes into account how historically this concept was developed, observing the controversies and discussions of a historical moment that led to the establishment of this concept. To this didactic approach we gave the name: Strategy based on historical facts. We verified that none of the texts consecrated in Higher Education of Physics use the last strategy to work on the concept entropy and we observed in current works of the area of physics teaching that the great difficulty in understanding this concept was directly related to the way it is treated in traditional texts. Taking into account the above, we apply the Strategy based on historical facts to the concept of entropy and we set up a new didactic strategy for this concept trying to solve the problems currently involved in understanding this phenomenon. We show how the entropy definition appears using the works of Carnot, Joule, Kelvin and Clausius. We present reasonable arguments for the unsustainability of strategies adopted by traditional textbooks when presenting this concept ignoring historical elements inseparable from the concept of entropy.
Das limitações histórico-conceituais das apresentações do conteúdo de entropia nos livros de física do ensino superior a uma proposta de ensino fundamentada em fatos históricos
Keywords: Entropy; History and Philosophy of Science; Second Law of Thermodynamics; Teaching Strategy